1989
DOI: 10.1101/gad.3.9.1273
|View full text |Cite
|
Sign up to set email alerts
|

Searching for pattern and mutation in the Drosophila genome with a P-lacZ vector.

Abstract: A P-element vector has been constructed and used to generate lines of flies with single autosomal P-element insertions. The lines were analyzed in two ways: (1) the identification of cis-acting patterning information within the Drosophila genome, as revealed by a lacZ reporter gene within the P element, and (2) the isolation of lethal mutations. We examined 3768 independent lines for the expression of lacZ in embryos and looked among these lines for lethal mutations affecting embryonic neurogenesis. This type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
356
3
7

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 663 publications
(374 citation statements)
references
References 60 publications
8
356
3
7
Order By: Relevance
“…Six different X-linked pGawB insertions were tested for transposition efficiency and ranged from 9.3% (MS1096) to 84.3% (Mz376.1). In contrast with previous reports (Brand and Perrimon, 1993;Gustafson and Boulianne, 1996), it is possible to achieve high frequency of GAL4 P-element comparable to pLacZ transposons (Bellen et al, 1989;Bier et al, 1989), indicating that the lower frequencies observed previously probably resulted from the genomic location of the starting pGawB insertion rather than a intrinsic feature. The chromosomal location and the effects of the insertion on the viability and the reproductive ability were determined for 468 lines (Table 1).…”
contrasting
confidence: 99%
“…Six different X-linked pGawB insertions were tested for transposition efficiency and ranged from 9.3% (MS1096) to 84.3% (Mz376.1). In contrast with previous reports (Brand and Perrimon, 1993;Gustafson and Boulianne, 1996), it is possible to achieve high frequency of GAL4 P-element comparable to pLacZ transposons (Bellen et al, 1989;Bier et al, 1989), indicating that the lower frequencies observed previously probably resulted from the genomic location of the starting pGawB insertion rather than a intrinsic feature. The chromosomal location and the effects of the insertion on the viability and the reproductive ability were determined for 468 lines (Table 1).…”
contrasting
confidence: 99%
“…In this experiment we used X-gal staining to detect b-galactosidase activity. This staining is mostly nuclear due to the nuclear localization signal of the transposase-b-galactosidase fused protein (Bier et al, 1989). In the heterozygous normal brain, the inner region of the brain hemispheres was stained (Figure 7a).…”
Section: Brat Gene Expressionmentioning
confidence: 99%
“…A third brat P-element strain, l(2)K11538, is probably a duplicate of strain l(2)K11523 (Spradling et al, 1999) since both were obtained from the same parents and may be derived from a premeiotic cluster. We veri®ed that each strain carries only one P-element used in the mutagenesis experiment (the P-lacW transposon, Bier et al, 1989), by restricting genomic DNA from these strains with enzymes that cut once within the transposon, and once in the adjacent genomic DNA. Under these conditions, restriction of transposons inserted in di erent sites yielded distinct restriction fragments, as predicted by the detailed map of the brat region (Figure 2a; data not shown).…”
Section: Reverting the Brat Phenotype By Tranposon Excisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional enhancers are often difficult to identify by a simple survey of genomic sequences since their nucleotide sequence are not well conserved and may be located several tens of kilobases from the site of transcription initiation. Enhancer trapping detects chromosomal enhancer elements in situ with minimal perturbations of the genome structure (Bellen et al, 1989;Bier et al, 1989;O'Kane and Gehring, 1987). A database of enhancer trap elements compiling their expression patterns and precise genomic locations should be extremely useful for studies of gene expression and genome analyses.…”
mentioning
confidence: 99%